Implementation of STEAM-Integrated Project-Based Learning Model with Ecoprint Techniques to Empower Students' Collaborative Skills - Ratnasari, Dwi; Murni, Dewi (Gemilang Maju Publikasi Ilmiah (GMPI), 2025)
This study aims to describe students' collaboration skillsin science learning based on Project Based Learning(PjBL) integrated with STEAM with ecoprinttechniques. The research method used is descriptivequantitative with a population of 6th grade students ofCipocok Jaya 1 Elementary School. Data were obtainedthrough observations of 12 indicators of collaborationskills covering aspects of participation, communication, teamwork, and problem solving, then analyzeddescriptively. The results showed that students' overallcollaboration skills were in the very high category withan average score of 83.3% and 81% of students were in the very good category. This indicates that theimplementation of the PjBL STEAM ecoprint model successfully empowered students' collaboration skills in completing projects involving effective interaction andtask division. The responsibility aspect showed thehighest score (85.88%). This study makes an importantcontribution to the development of 21st century learning that emphasizes collaboration as a corecompetency.